Interdisciplinary perspectives in subject analysis - Rocha, Maria Meriane Vieira (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2021)
In Information Science context, Subject Analysis is considered one of the most important stages in Indexing and the indexer is the reponsible for this activity. An interdisciplinarity with Linguistics, Cognitive Science and Logics is observed during the development of this activity by the indexer. The study discusses factors of these areas that interfere in Subject Analysis. Linguistic factors act in concert with logical and cognitive factors in the intellectual activities that comprise Subject Analysis. So close is their interaction that it is not possible to determine where the influence of one begins or finishes. Link: http://www2.marilia.unesp.br/revistas/index.php/bjis/article/download/8023/5642/